The Effect of Omega-3 Fatty Acids on ARDS: A Randomized Double-Blind Study - Masoud Parish; Farnaz Valiyi; Hadi Hamishehkar; Sarvin Sanaei; Mohammad Asghari jafaabadi; Samad EJ EJ Golzari; Ata Mahmoodpoor (Tabriz University of Medical Sciences, 2014)
Purpose: The aim of this study was to evaluate the effect of an enteral nutrition diet, enriched with omega-3 fatty acids because of its anti-inflammatory effects on treatment of patients with mild to moderate ARDS. Methods: this randomized clinical trial was performed in two ICUs of Tabriz University of Medical Sciences from Jun 2011 until Sep 2013 in north west of Iran. Fifty-eight patients with mild to moderate ARDS were enroled in this clinical trial. All patients received standard treatment for ARDS based on ARDS network trial. In intervention group, patients received 6 soft-gels of omega-3/day in addition to the standard treatment. Results: Tidal volume, PEEP, pH, PaO2/FiO2 , SaO2, P platue and PaCO2 on the 7th and 14th days didn't have significant difference between two groups. Indices of lung mechanics (Resistance, Compliance) had significant difference between the groups on the 14th day. Pao2 had significant difference between two groups on both 7th and 14th days. Trend of PaO2 changes during the study period in two groups were significant. We showed that adjusted mortality rate did not have significant difference between two groups. Conclusion: It seems that adding omega-3 fatty acids to enteral diet of patients with ARDS has positive results in term of ventilator free days, oxygenation, lung mechanic indices; however, we need more multi center trials with large sample size and different doses of omega-3 fatty acids for their routine usage as an adjuant for ARDS treatment.